Privacy Protection: YOLOv11 Face Detection and Blurring for GDPR Compliance in Hotels - khan, Mohammed Ikramullah; B., Vivekanandam (Journal of Innovative Image Processing, 2025)
Surveillance systems have undergone a drastic transformation over the years, with the advent of artificial intelligence (AI) in surveillance paving the way for better security and monitoring in public as well as private places, including hotels. But not without its considerable privacy implications since the introduction of the European Union (EU) law, the General Data Protection Regulation (GDPR), which aims to protect the privacy of EU citizens. The surveillance system collects sensitive guest data from personal information, facial data, and general appearance, making it paramount that hotels adhere to mandatory data protection laws such as the General Data Protection Regulation (GDPR) for visitors in the EU, to ensure that the data is not misused or accessed by unauthorized individuals. A privacy-protection framework for face detection and anonymization in hotel surveillance systems has been designed in this research to protect privacy from surveillance cameras based on YOLOv11, a top-tier convolutional neural network (CNN) model. The system checks for faces in video feeds/images and accurately applies a blurring mechanism, successfully anonymizing identities. The process is designed to comply with GDPR regulations while preserving essential capabilities of surveillance systems through anonymization. One of the inherent challenges is ensuring the privacy of the individuals going about their day-to-day business in front of such surveillance cameras, and at the same time, ensuring that the footage that could possibly be shared with authorities or even other stakeholders is useful. Such integration of YOLOv11 in hotel surveillance systems showcases the potential of artificial intelligence to provide security without compromising privacy.